2009
DOI: 10.1111/j.1471-6712.2008.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and pregnancy: women’s opinions about the care provided during the childbearing year

Abstract: Satisfaction with care was shown. A discussion about the implication of informed choice with both staff and mothers are needed. Sharper implementation of the diabetes-care-chain was also an area for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Our results are consistent with other studies that have found that postpartum women feel inadequately prepared for the postpartum period [3, 1618]. Women in our maternal focus groups also expressed dissatisfaction with the communication and preparation they had received for discharge.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with other studies that have found that postpartum women feel inadequately prepared for the postpartum period [3, 1618]. Women in our maternal focus groups also expressed dissatisfaction with the communication and preparation they had received for discharge.…”
Section: Discussionsupporting
confidence: 91%
“…This review found that such information was not always available to women, in particular those living in rural communities [28]. A study investigating opinions about care during pregnancy, childbirth and postnatally among women with T1DM and gestational diabetes found that staff in different areas of care might need more knowledge about diabetes to reduce the risk of women receiving inadequate/incorrect information [49]. The authors concluded more effort must be expended on procedures and written materials, to ensure that women are better prepared and that the information flow throughout the care chain is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this approach, which we may refer to as an outside approach, is a finding that corresponds with the results of other studies. 10,25,26 We found that the women valued the visible and audible part of the consultation: being able to actually see their baby on the screen and hear its heartbeat with the Doppler. As noted by Berg and Honkasalo, 27 women with a high-risk pregnancy more easily lose touch with their own body and accept objective knowledge that is more correct and valuable.…”
Section: The Outside and Inside Approachmentioning
confidence: 90%